Polìgraf u Pol’ŝì ta Ukraїnì : ìstorìâ, sučasnij stan ì perspektivi - Kogutič, Ivan (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2011)
The article deals with the issue of history, current state and prospects of the polygraph application in legal proceedings and other spheres of legal regulation in Poland and Ukraine.
Keywords: Polska; Ukraina; kryminalistyka; wariograf; badania wariograficzne; metoda poligrafii